Draft Annual Plan 1987-88 Vol. I General Profile Government of Uttar Pradesh - Planning Commission (Planning Commission, 1986)
The State of Uttar Pradesh is roughly located between 77° and 84°. east longitude and 25° and 31° north latitude. It is bounded on the north by Himalayas and on the south by the State of Madhya Pradesh. The Union Territory of Delhi and the States of Haryana and Rajasthan adjoin it to the west and the State of Bihar to the east.
Government of Uttar Pradesh, Planning Department